ASN Personnel Reform in the TNI AD - Subroto, Ismail Gatot; Indriati, Fibria (Journal of Law, Politic and Humanities, 2024)
The role and position of Civil Servants (PNS) is very significant because they are an integral part of the state apparatus who are responsible for carrying out government tasks to achieve national goals. Civil servants function as public servants loyally to Pancasila and the 1945 Constitution. However, the performance of civil servants is often subject to negative scrutiny from various circles, and the mass media often report about lack of productivity, waste of state budget, lack of discipline, and low work ethic of civil servants. This stigma generally covers various government agencies. To overcome this problem, corrective steps need to be taken, including through human resource development. This aims to change society's negative views and strengthen civil servants in facing increasingly fierce local and global competition. Law No. 5 of 2014 concerning the State Civil Apparatus stipulates that the State Civil Apparatus must be considered a profession that has the obligation to manage and develop itself and is responsible for its performance. Employee performance is measured based on predetermined quality and quantity standards. Employees who perform well are considered as organizational assets who strive to continuously improve themselves, support organizational productivity, and motivate themselves systematically. Motivation development includes increasing knowledge, work skills, mental attitudes, and work environments that stimulate individual work satisfaction and willingness. TNI AD Civil Servants have a complementary role to TNI AD Soldiers, are responsible for non-combat administrative tasks, and have career development opportunities that are equivalent to the development of knowledge within the TNI AD organization. Organizations cannot avoid changes as a result of national policies. Therefore, civil servant organizations within the TNI AD need to adapt to changing situations and conditions in carrying out their duties. In facing developments in science and technology as well as intense competition, all components in TNI AD agencies, including TNI members and TNI-AD civil servants, need to support improving the quality of human resources through internal improvements, including human resource development. In carrying out the duties and functions of the Indonesian Army, quality human resource support is a must. The quality of human resources is a key factor for increasing the productivity and contribution of an organization or agency. Therefore, high motivation is needed to support increased employee work performance, although civil servant performance assessments cannot only be measured through Employee Performance Targets (SKP), because there is a gap between expected performance and actual performance. Nevertheless, hopes for the improvement of human resources within the Indonesian Army (TNI AD), especially the Civil Servants of the Indonesian Army (PNS TNI AD), have been bolstered with the enactment of Law No. 20 of 2023 aimed at enhancing the professionalism of Civil Servants (ASN) in Indonesia, including Civil Servants within the Indonesian Army, and the introduction of Government Employees with Work Agreements (PPPK). This law highlights several crucial aspects of ASN management, such as strengthening the supervision of the merit system, determining the needs of PNS and PPPK, improving welfare, organizing honorary staff, and digitizing ASN management. Its main focus is to enhance transparency, accountability, and the quality of public services by eliminating nepotism, corruption, and political interference in ASN management to support the main tasks of the Indonesian Army. Specific measures like open promotions, the establishment of competency-based PPPK, and protection from political interference are expected to strengthen the merit system in bureaucracy, fostering healthy competition among employees to enhance their competence and professionalism. It is hoped that this law will create a more professional and efficient ASN within the Indonesian Army; nationally, the success of its implementation will depend on support from various parties in effectively managing the change. Overall, a merit-based human resource management approach is expected to shape a reliable and integrity-driven Civil Servant apparatus, PNS, and PPPK, in serving and supporting the primary tasks of the Indonesian Army as the frontline protectors and guardians of the nation. Therefore, this article will discuss the reforms in ASN personnel management within the Indonesian Army.  Therefore, this article will discuss how to reform ASN personnel in the TNI AD.